Typology of after-hours care instructions for patients: Telephone survey and multivariate analysis - Bordman, Risa (College of Family Physicians of Canada, 2007)
OBJECTIVE: To develop a typology of after-hours care (AHC) instructions and to examine physician and practice characteristics associated with each type of instruction. DESIGN: Cross-sectional telephone survey. Physicians’ offices were called during evenings and weekends to listen to their messages regarding AHC. All messages were categorized. Thematic analysis of a subset of messages was conducted to develop a typology of AHC instructions. Logistic regression analysis was used to identify associations between physician and practice characteristics and the instructions left for patients. SETTING: Family practices in the greater Toronto area. PARTICIPANTS: Stratified random sample of family physicians providing office-based primary care. MAIN OUTCOME MEASURES: Form of response (eg, answering machine), content of message, and physician and practice characteristics. RESULTS: Of 514 after-hours messages from family physicians’ offices, 421 were obtained from answering machines, 58 were obtained from answering services, 23 had no answer, 2 gave pager numbers, and 10 had other responses. Message content ranged from no AHC instructions to detailed advice; 54% of messages provided a single instruction, and the rest provided a combination of instructions. Content analysis identified 815 discrete instructions or types of response that were classified into 7 categories: 302 instructed patients to go to an emergency department; 122 provided direct contact with a physician; 115 told patients to go to a clinic; 94 left no directions; 76 suggested calling a housecall service; 45 suggested calling Telehealth; and 61 suggested other things. About 22% of messages only advised attending an emergency department, and 18% gave no advice at all. Physicians who were female, had Canadian certification in family medicine, held hospital privileges, or had attended a Canadian medical school were more likely to be directly available to their patients. CONCLUSION: Important issues identified included the recommendation to use an emergency department as the sole source of AHC, practices providing no specific AHC instructions to their patients, and physicians’ lack of acceptance of Telehealth. To improve AHC, new initiatives should build upon the existing system, changes should be integrated, and there should be a range of AHC options for patients and physicians.